The Impact of Poverty Reduction Program into Papuan Women Economy Behavior in District of Kemtuk Gresi, Jayapura Regency (Case Study) - De Quelyoe, Flora Yvonne; Ratang, Sarlota; Wakarmamu, Christine Marina (Journal of Education and Vocational Research, 2016)
Based on The Intenasional Summit which had launced the 8th important issues on Millenium Development Goals (MDGs), is very usefull to improve the communitylife. The quality of women’s life has been one of basic aspects to build sustainable development of a nation (Khofifah, 1998). Sustainable development can take place if the entire communities (men and women) being optimally involved in whole development program with using efficient and effective principles. The quality of life is largerly determined by formal and non formal education, both poor degree of health and nutrition, buruknya derajat kesehatan dan gizi, and also the presence of accessbility to development resources. Those factors mentioned above are mutual supporting and can not be separated from one another. Although, development activity in Papua Province is growing up, the society is still livingin the cycles of poverty, especially for women in District of Kemtuk Gresy, Jayapura Regency, Province of Papua. The aims of the study are : 1) to know the impact of Poverty Reduction Program (into the changing of economy behavior of Papuan Women in Kemtuk Gresi, Jayapura Regency, Papua Province; 2) to explore how Poverty Reduction Program influenced the generating income of Papuan Women. The methods of data collection are in-depth interview to 150 respondents, and 5 key informants (Community, Traditional, Religion, Women, and Youth Leaders), and observation as well. In order to find the answer, is using descriptive qualitative. The result of the first research question indicated that in terms of Changing of economic behavior: 34 percent of Papuan Women in Kemtuk Gresi are changing their economic behavior, mainly their production and marketing strategy; whereas 66 percent of respondents are still in traditional way for production and marketing. The second result is 38 percent of respondent’s income is increasing, and 44 percent respondents are remains static or even volatile, finally, 18 percent respondents are going out from economic activities, because of missing capital of business. Starting from the result, we can give some recommendations: 1) changing economic behavior should be started from young people, so all parties should participate intensively to push young women entrepreneur to engage in business activity; 2) the government should involve traditional leaders to support women entrepreneurs by providing a piece of land or other forms of capital.